PENYEBAB ANAK PUTUS SEKOLAH DI DESA TUMBANG KAMINTING KECAMATAN BUKIT SANTUAI - Mahmuddin Mahmuddin; Siti Halimah; Wardania Wardania (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2019)
The school drop out rate always increases every year and many factors cause children to decide to quit school. This study aims to determine the causes of school dropouts in Tumbang Kaminting Village, Bukit Santuai District. This study is a qualitative descriptive study that carries out stepwise data analysis, data reduction, data presentation, and ended with the conclusion by interviewing out of school children as research subjects. And to test the validity of the data using the source triangulation technique to parents, neighbors and peers of research subjects. The results of the analysis show that the causes of school dropouts are 1) because of severe illness and, 2) because the school was considered interesting.